(untitled) (Journal of Medical & Health Sciences Review, 2025)
The postpartum period is critical for maternal and newborn health, marked by significant physiological and emotional changes. Cultural and traditional dietary practices often play a vital role in restoring maternal health and promoting lactation. This study investigates the proximate composition, mineral content, total phenolic content, and antioxidant activity of traditionally consumed postpartum supplemental foods in eight districts of Khyber Pakhtunkhwa, Pakistan. Data were collected from postpartum women through interviews, and commonly consumed foods were selected for chemical analysis. The findings reveal that these foods are nutrient-dense, with significant amounts of macronutrients, minerals, and bioactive compounds. The study highlights the role of traditional dietary practices in maternal nutrition while emphasizing the need for a balanced approach combining cultural practices and medical guidelines. These insights can aid healthcare professionals in optimizing dietary plans for lactating mothers, ensuring improved maternal and neonatal health outcomes.